Laying Africa’s roads to prosperity - Michael Fleshman (Africa Renewal, 2009)
From outer space the vast Cahora Bassa hydroelectric complex on the Zambezi River in Mozambique is easy to see. Originally built by the Portuguese colonial authorities and later transferred to Mozambican ownership, the dam has huge turbines that generate enough electricity to power millions of homes and businesses in South Africa and the surrounding region.